Distribution And Abundance of Flamingos (Phoenicopteriformes: Phoenicopteridae) In the Salt-Affected Wetlands of The Peruvian Andes - Canales-Gutiérrez, Ángel; Pillco-Mamani, Katia; Canales-Manchuria, Gelvi; Chambi-Alarcon, Marisol Sheyla; Mestas-Gutierrez, Nataly Irene; Belizario-Quispe, Germán; Canales-Manchuria, Fabrizzio (International Journal of Membrane Science and Technology, 2023)
This study investigates the distribution and abundance of flamingos (Phoenicopteriformes: Phoenicopteridae) in salted high-Andean wetlands of Peru. These wetlands are located at an altitude between 3 200 and 4 600 meters above sea level and represent key habitats for these birds. However, there is little information about the presence of flamingos in these environments and their relationship with salinity. To analyze the distribution and abundance of flamingo species in the salted wetlands of the Peruvian Andes. Sampling was carried out in 11 wetlands over a period of time from August to October 2021. Both adult and juvenile individuals were recorded, and data on physicochemical water parameters and environmental variables were collected. They reveal interesting patterns regarding the distribution and abundance of flamingos in these salted wetlands. It was observed that the Loriscota wetland harbors the largest population of flamingos, with a total of 14 750 individuals belonging to the species Phoenicopterus chilensis, Phoenicoparrus andinus, and Phoenicoparrus jamesi. Among these species, Phoenicopterus chilensis was the most abundant. Furthermore, a positive correlation was found between the presence of flamingos and certain environmental and physicochemical parameters. Water pH, maximum ambient temperature, and relative humidity showed a significant association with the presence of flamingos in the wetlands. This study provides important information about the distribution and abundance of flamingos in the salted high-Andean wetlands of Peru, which will contribute to the understanding of interactions between flamingos and their habitat. Additionally, they will serve as a basis for future conservation and management strategies for these species and the wetlands.